Low Level Laser Therapy to Reduce Recurrent Oral Ulcers in Behçet’s Disease - D. B. Gandhi Babu; Sunanda Chavva; Shefali Waghray; Neeharika Satya Jyothi Allam; Marella Kondaiah (Case Reports in Dentistry)
Behçet’s disease (BD) is a chronic, relapsing multisystemic vascular condition. Behçet’s disease was described by Hulusi Behçet in 1937. This rare multisystem relapsing-remitting inflammatory disease is poorly understood but is thought to be an autoimmune inflammatory vasculitic process in a genetically predisposed population. Diagnosis of Behçet’s disease is based on International Criteria of Behçet’s Disease (ICBD). The present paper describes a case report of Behçet’s syndrome where aphthous stomatitis was treated with low level laser therapy.